Pedofilia dalam Perspektif Hukum Perlindungan Anak di Indonesia - Samsul Huda; Santoso, Yudi (Policy and Law Journal, 2025)
Pedophilia is a form of sexual violence against children that causes serious impacts on children’s physical, psychological, and social development. This phenomenon demands a legal response that is not only repressive in nature but also oriented toward protection and victim recovery. This study aims to analyze pedophilia from the perspective of child protection law in Indonesia, including normative regulation, forms of legal protection for victims, and problems in law enforcement. The research method used is normative legal research with statutory and conceptual approaches. The results show that Indonesian positive law has substantively qualified pedophilia as a form of sexual violence against children through various laws and regulations, although it has not been explicitly and integratively formulated. Legal protection for child victims of pedophilia has been regulated in preventive, repressive, and rehabilitative forms; however, its implementation still faces structural and cultural obstacles. Law enforcement that has not fully oriented toward the best interests of the child causes the protection provided to be not yet optimal. Therefore, comprehensive and sustainable strengthening of legal protection is required to ensure the rights and recovery of child victims of pedophilia.